Moringa oleifera L. sebagai Solusi Sosioekonomi dan Kesehatan Masyarakat dalam Menghadapi Pandemi Covid-19 di Bengkulu - Risnita Tri Utami; Marlinah Marlinah (Abdihaz: Jurnal Ilmiah Pengabdian pada Masyarakat, 2021)
Moringa oleifera L. for Socioeconomic and Public Health Solutions in Facing the Covid-19 Pandemic in Bengkulu The Corona virus (COVID-19) which causes disorders of the human respiratory system has spread rapidly in various parts of the world. One of Universitas Prof. Dr. Hazairin, SH's efforts in providing solutions to the community during this pandemic was through community service activities. The target of the community service activities were residents who fall into the middle to lower economic class category in Pasar Baru, Pasar Melintang, and Jitra sub-districts, Teluk Segara district. The purpose of this program was to help empower the community to increase awareness of maintaining health and environmental hygiene as well as improving the economy through additional income from sales of moringa processed products. The methods used in this activity were socialization, education on the benefits of moringa, and training for the use of moringa. The results of the activity showed that the enthusiasm of the community was high. It could be seen from the seedlings of moringa that were given to life target residents reaching 94%. Furthermore, the understanding of the benefits of moringa increased during this program. The high enthusiasm was also seen from the village employees, PKK women, and youth groups to attend training on moringa processed products. Community service has been carried out well and received very good attention from community members in Pasar Baru, Pasar Melintang, and Jitra sub-districts.